Health resource utilisation associated with skeletal‐related events in patients with bone metastases secondary to solid tumours: regional comparisons in an observational study. (10th February 2016) - Duran, I.; Fink, M.G.; Bahl, A.; Hoefeler, H.; Mahmood, A.; Lüftner, D.; Ghazal, H.; Wei, R.; Chung, K.C.; Hechmati, G.; Green, J.; Atchison, C.
Abstract : Skeletal‐related events (SREs) including spinal cord compression, pathologic fracture, and radiation or surgery to bone, occur frequently due to bone metastases in advanced cancer. This analysis of a multicentre, observational study was designed to describe cross‐regional differences in health resource utilisation (HRU) of SREs in Western Europe and the US. Patients with bone metastases due to breast, lung or prostate cancer, or multiple myeloma who had experienced a SRE within the past 97 days were enrolled. Investigators recorded HRU associated with SREs, including hospitalisation and length of stay (LOS), outpatient visits, procedures and bisphosphonate use. This subanalysis includes 668 patients with solid tumours (US, n = 190 with 354 SREs; EU, n = 478 with 893 SREs). The rate of SREs associated with hospitalisation(s) was higher in the EU vs. the US (30% vs. 15%, P < 0.001) and LOS was longer in the EU [mean (SD) days/SRE: 19.87 (17.31) vs. 10.61 (9.39)]. However, the US was associated with higher rate of SREs with outpatient visits than the EU (88% vs. 74%, P < 0.0001) and more procedures [mean (SD)/SRE: 11.26 (7.94) vs. 6.91 (6.48)]. Bisphosphonates were less often used in the EU (65% vs. 76% of US, P = 0.0033). In patients experiencing SREs due to bone metastases, HRU patterns reflect regional diversity with a substantial burden in both regions.